A bridge of longing the lost art of Yiddish storytelling - Roskies, David G. 1948- (Harvard Univ. Press, 1995)
Focuses on authors: Nahman of Bratslav, Isaac Meir Dik, I.L. Peretz, Sholem Aleichem, Der Nister, Itzik Manger, and Isaac Bashevis Singer.
Keywords: Jiddisch; Mondelinge literatuur; Storytelling; Yiddish literature -- History and criticism; Erzählen; Prosa